FAKTOR-FAKTOR RISIKO PENULARAN HIV/AIDS PADA LAKI-LAKI DENGAN ORIENTASI SEKS HETEROSEKSUAL DAN HOMOSEKSUAL DI PURWOKERTO - DL, Agung Saprasetya; Dwi Lestari, Diyah Woro (Jurusan Kedokteran FK Unsoed, 2010)
Indonesia is a country with the highest HIV/AIDS cases acceleration in the world. Purwokerto hasa high number of HIV/AIDS cases, rank number two in Central Java Province. However, risk factor forHIV/AIDS transmission among high risk groups, especially among men who have sex with men, has notbeen identified. This research aimed to examine HIV/AIDS transmission risk factors among homosexualand heterosexual men in Purwokerto. This study is a cross sectional study. Study population is all menaged at least 17 years old living in Purwokerto and its surrounding area. Sampling method used wassnowballing sampling. Data were collected with a quessionere. The result shows that homosexual men hashigher risk to suffer from HIV/AIDS through sexual behavior, these are having sex with multiple partner.No differences in HIV/AIDS transmission risk factors by parenteral and sexually transmitted disease werefound between homosexual and heterosexual men. In conclusion, homosexual men have higher risk factorsfor the transmission of HIV/AIDS than that of heterosexual men, especially through sex partner more thanone and anal sex.